Failure to bloom: Intense upwelling results in negligible phytoplankton response and prolonged CO2 outgassing over the Oregon shelf. Issue 3 (5th March 2015) - Evans, Wiley; Hales, Burke; Strutton, Peter G.; Shearman, R. Kipp; Barth, John A.
Abstract During summer, upwelled water with elevated CO2 partial pressure (pCO2) and nutrients outcrops over the Oregon (OR) inner shelf. As this water transits across the shelf, high rates of primary production fueled by the upwelled nutrients results in net atmospheric CO2 drawdown. Upwelled source‐waters typically have pCO2 approaching 1000 µatm that is then reduced to ∼200 µatm. For almost the entire month of July 2008, strong and persistent upwelling brought cold (∼8°C), saline (∼33.5), high‐pCO2 (>600 µatm) water to our midshelf buoy site, and high‐pCO2 water was broadly distributed over the shelf. Chlorophyll levels, as a proxy for phytoplankton biomass, were low (< 2 mg m−3) on the shelf during the period of most intense upwelling, and satellite data showed no evidence of a downstream phytoplankton bloom. A small chlorophyll increase to ∼4 mg m−3 was observed at our buoy site following a decrease in the strength of southward wind stress 10 days after upwelling initiated. Chlorophyll levels further increased to ∼10 mg m−3 only after a cease in upwelling. These higher levels were coincident with the appearance of water masses having temperature and salinity properties distinct from recently upwelled water. We suggest that rapid offshore transport and subsequent subduction before phytoplankton populations could respond is the most likely explanation for the persistent low chlorophyll and elevated surface‐water pCO2 throughout the July upwelling event. This mechanism likely dominates under conditions of strong and persistent upwelling‐favorable winds that coincide with close proximity of low‐density offshore waters, which may have implications for the biogeochemical functioning of this system under future climate scenarios.